The Development of Webbed Model-Based Integration Learning in Improving Arabic Mastery - Buska, Wahyudi; Nasir, Nasir; Prihartini, Yogia (Universitas Islam Negeri (UIN) Sulthan Thaha Saifuddin Jambi, 2024)
This study aimed to determine the conditions of learning implementation and develop an integrated Arabic learning model. The research subjects were students of the Department of Arabic Language and Literature, Faculty of Adab and Humanities, Semester 1 (one) and Semester 3 (three), totaling 60 people. A development model was used as the research methodology. The process involved designing and developing an integrated learning model in the field of education after obtaining data from the results of a survey conducted on the subject under study. Based on the facts in the field, it shows that Arabic language learning in the Arabic Language and Literature Department, Faculty of Adab, and Humanities needs to be improved. One way to accomplish this is to develop an integrated learning model that can combine Arabic language knowledge in the learning process so that it is hoped that students will be able to master Arabic language knowledge as a whole. The results of this research can be used as material for consideration as an alternative in efforts to develop an integrated learning model for teaching Arabic.